Redes de valor semânticas - Reis, Jefferson da Silva (2018)
Value network models comprise commercial transactions among business actors which cooperate to satisfy the needs of a market segment. These models can be used as a decision support mechanism for market analysis and exploitation. However, knowledge sharing is still a problem in value network modeling. For that purpose, ontologies have been used to establish a common language among business analysts involved in decision making within the enterprises. This research proposes an ontology for modeling semantic value networks. The ontology is supposed to be used as a decision support mechanism for executives, combining concepts of Multiple Agency Theory, Enterprise Ontology, Value Network Modeling and Speech Acts Theory. Its modeling goal is to support a machinereadable representation and semi-automatic assembling of the constituents of a value network. Currently, Value Network Modeling still demands substantial handcraft and tacit knowledge from business analysts familiar with this modeling technique. The ontology was designed based on a systematic literature review in value network modelling and refined by application in three observational case studies. After the refinement phase, partial validation was achieved by means of Technical Action Research on an ongoing real-world case study in a Pakistani Telecom organization, which heavily relies upon e-Commerce for service retailing and customer evaluation